Income distribution: Signs of a trend reversal in the poverty risk; single parents less frequently at risk of poverty - Markus M. Grabka (DIW Weekly Report, 2025)
Despite high inflation, the real gross hourly wages of employees grew by around 15 percent from 1995 to 2022. In particular, the lowest wage decile caught back up to all other deciles following a sharp drop in real wages. At the same time, the low-wage sector has shrunk by nearly five percentage points since 2007, and by even more in the east of Germany (14 percent). In 2022, 18.5 percent of employees had their main occupation in the low-wage sector. In inflation-adjusted terms, net household income has increased by 35 percent on average since 1995. After a long period in which the poverty risk grew, the trend finally seems to be shifting in the other direction. Across Germany, the poverty risk has declined by 4.3 percentage points for single parents since 2010; in the east, this decline was by 14.5 percentage points. If policymakers' aim is to reduce the poverty risk, they should focus on children and youth, as the dropout rate has increased to 13.1 percent. Without a degree, a person is more likely to take a low-paying job that puts them at risk of poverty. Targeted education expenditure, which could be financed via wealth taxes, is very much needed for this reason.
Keywords: D31; I31; I32; J31; 330; Wages; working poor; Household Income; poverty; lone parents; SOEP